2017
DOI: 10.1158/1078-0432.ccr-17-1449
|View full text |Cite
|
Sign up to set email alerts
|

Underreporting of Research Biopsies from Clinical Trials in Oncology

Abstract: PURPOSE Research biopsies are frequently incorporated within clinical trials in oncology, and are often a mandatory requirement for trial enrollment. However, limited information is available regarding the extent and completeness of research biopsy reporting. METHODS We identified a cohort of therapeutic clinical trials where non-diagnostic research biopsies were performed between January, 2005-October, 2010 from an IR database at our institution. Clinical trial protocols were compared with the highest level… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 43 publications
0
15
0
1
Order By: Relevance
“…Use of actual tumour biopsies in clinical trials is being recommended to improve characterization of the pharmacodynamic effects of a drug, to understand the molecular processes involved in drug response or resistance, and to identify prognostic and predictive markers (Parseghian et al 2017 ). In general, new tumour material is difficult to acquire, either because of refusal of the patient, the location is difficult to reach or because of inadequate sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Use of actual tumour biopsies in clinical trials is being recommended to improve characterization of the pharmacodynamic effects of a drug, to understand the molecular processes involved in drug response or resistance, and to identify prognostic and predictive markers (Parseghian et al 2017 ). In general, new tumour material is difficult to acquire, either because of refusal of the patient, the location is difficult to reach or because of inadequate sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Prior investigations have found that a high rate of clinical trials in oncology remain unpublished. [3][4][5][6][7][8] Due to these findings, recent regulations have been enacted to require clinical trial result reporting. 9 However, these efforts are limited to outcome measures that are part of a clinical trial's statistical analysis plan, and thus are unlikely to include most research biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, however, research biosampling often leads to translational research overload, especially when the results of such analyses are underreported or never reported. [18][19][20]…”
Section: Streamline Required Study Evaluationsmentioning
confidence: 99%
“…With regard to translational and pharmacodynamics studies, there is no doubt that research biopsies and other assays can yield critical insights and drive scientific progress. Conversely, however, research biosampling often leads to translational research overload , especially when the results of such analyses are underreported or never reported 18‐20 …”
Section: Recommendationsmentioning
confidence: 99%